A Thermodynamically Consistent Port-Hamiltonian Model for Dielectric Elastomer Membrane Actuators and Generators. Issue 1 (July 2017) - Rizzello, G.; Naso, D.; Seelecke, S.
Abstract: This paper presents a port-Hamiltonian modeling formulation for a Dielectric Elastomer membrane. The model relates electrical and mechanical inputs to corresponding conjugate outputs, allowing to simulate the membrane transducer in actuation and energy harvesting application. Starting from a nonlinear, physics-based model developed in the authors' previous works, a suitable function is initially proposed to quantify the overall electro-mechanical energy in the system. Subsequently, a complete description in terms of Hamiltonian, dissipation function, and system matrices is provided. The port-Hamiltonian formalism permits to assess the thermodynamic consistency of the model, making it a reliable tool for the prediction of energetic performance in dynamic applications. Furthermore, it opens up the possibility of applying powerful nonlinear analysis and design tools.